2015
DOI: 10.1097/md.0000000000001835
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Preterm Infants With Postnatal Cytomegalovirus Infection via Breast Milk

Abstract: Approximately 15% of preterm infants may develop postnatal cytomegalovirus (CMV) infection from seropositive mothers via breast milk and are at risk for neurological sequelae in childhood. The aims of this study were to assess the effects and outcomes on growth, neurodevelopmental status, and hearing in very low birth weight (VLBW) premature infants with postnatal CMV infection via breast milk at the corrected age of 12 and 24 months.The prospective follow-up study population comprised all living preterm child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 33 publications
1
71
3
Order By: Relevance
“…Among the few studies reporting longer--term follow--up of premature infants (<1500g birth weight) with postnatal CMV acquisition, some found no significant differences in outcomes compared to controls, while others suggested mild neurocognitive impairments 31--33 . Unlike congenital CMV infection, no sensorineural hearing loss has been found 31,33 .…”
Section: CMVmentioning
confidence: 97%
“…Among the few studies reporting longer--term follow--up of premature infants (<1500g birth weight) with postnatal CMV acquisition, some found no significant differences in outcomes compared to controls, while others suggested mild neurocognitive impairments 31--33 . Unlike congenital CMV infection, no sensorineural hearing loss has been found 31,33 .…”
Section: CMVmentioning
confidence: 97%
“…Some follow-up studies indicated poor neurocognitive outcome in adolescents born preterm with postnatal CMV infection 43,44) . In contrast, other studies showed that preterm infants might not have an increased risk for neurological sequelae after CMV postnatal infection 9,45) .…”
Section: Resultsmentioning
confidence: 57%
“…About 30%‐50% of neonatal CMV infections are caused by recurrent infection in pregnant women, and the pathogenesis of BM‐acquired CMV infection may be relevant to immunodeficiency of the infants. The BM‐acquired CMV infection rates in premature and low‐birthweight infants differ among countries; however, there are few data about BM‐acquired CMV infection in jaundiced neonates . Our study results show that the BM CMV‐DNA (+) rate was 32.67% (98/300 cases) and the BM‐acquired CMV infection rate was 18.37% (18/98 cases) among the 300 pathologically jaundiced infants.…”
Section: Discussionmentioning
confidence: 64%